The Importance of Trade for Reverend E. M. Lijadu and the Evangelist Band Mission - Joseph Osuolale Ayodokun (Yoruba Studies Review, 2021)
This article discusses the activities of the Evangelist Band Mission (EBM), led by Reverend E. M. Lijadu from 1901 to his death in 1926, in the coastal Ikale and Ilaje areas south of Ondo. The EBM whih operated in close association with the Church Missionary Society, but was financially independent and self-supporting. Trade was an important factor in ensuring its economic viability. The article also suggests that the availability of goods associated with Christianity, such as books, Western dress, and certain tools, was a factor that contributed to the adoption of Christianity because it allowed individuals to ‘try out’ forms of consumption associated with Christianity in a positive and yet containable way.